Superior Mesenteric Artery Thrombosis; Rare complication after Pancreaticoduodenectemy - Jindal, Satyaprakash; K., Adithya G.; Hukkeri, Vachan; Madaan, Varun; Chitra; Vohra, Sandeep; Tandon, Vivek; Govil, Deepak (Journal of Health and Allied Sciences NU, 2018)
Pancreaticoduodenectemy(PD) is the treatment of choice for malignant and some benign diseases of the pancreas and periampullary region. Common complications after PD include delayed gastric emptying, pancreatic fistula, anastomotic leak and intra abdominal collection. Postoperative medical complications include arrhythmia, renal failure, pulmonary complications, UTI and Deep vein thrombosis. Superior mesenteric artery (SMA) thrombosis is rarely been reported after PD. There is theoretical possibility of arterial thrombosis in patient with history of vascular disease, which may precipitate after postoperative hypovolemia. SMA thrombosis is difficult to diagnose in postoperative period due to nonspecific symptoms and associated with high mortality rate up to 80-90%. Our patient was a 68 years old female with lower end cholangiocarcinoma without any other co-morbidity. She underwent PD without any intraoperative complications. Post operatively she developed SMA thrombosis. Unfortunately patient could not be salvaged and she succumbs to death.
Keywords: SMA thrombosis; Pancreaticoduodenectemy; cholangiocarcinoma